Ananalyse The victims of Bullying About Junior High School Students in Pekanbaru - Arlizon, R.; Putra, Roby Maiva; Saam, Zulfan; Rahmadani, Fiska Dwi; Azmi, Rini Wil (Proceedings of the UR International Conference on Educational Sciences, 2018)
Bullying cases are a lot of cases in the education world, especially in Indonesia. Bullying is a negative behavior that can adversely affect the physical and psychological development of individuals including their self confidence. This study aims to describe: (1) the level of bullying in junior high school students, (2) the differences of bullying in junior high school students based on gender, (3) the level of self-confidence of bullying victims. The sample of this research was junior high school students in Pekanbaru. The technique of sample used purposive sampling and there was 500 students of bullying victims. This research was descriptive quantitative. The results of this study was: (1) most of the bullying experienced by students was in the medium category, (2) there was significant differences between bullying experienced by male students and female students, (3) the level of self-confidence of the victims bullying was mostly in the medium category.